Impact of Climate Change and Natural Disasters on Livelihoods in Northern Mountainous Regions of Vietnam: A View from Dien Bien Province - Tho Hung, Ngo; Long, Trinh Tuan; Kim Ngoc Anh, Nguyen; Thi Hong Nhung, Tran; Thi Hong Ngoc, Nguyen; Anh Quan, Tran; Thanh Van, Pho; Van Phuong, Do (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 4DO - 10.25073/2588-1094/vnuees.5110, 2024)
This study examines impacts of climate change and natural disasters on livelihoods in Dien Bien province, located in Northern Mountainous Region of Vietnam. Based on meteorological data, household surveys, interviews, and focused group discussions conducted across four communes, the research finds that Dien Bien is experiencing more frequent and intense extreme weather events, including heavy rainfall, landslides, and droughts. These changes are severely impacting agriculture-dependent ethnic minority communities, with over 60% of households reporting arable land and crop productivity losses of 40-65% in 2022 alone. Income losses are the most pronounced in remote areas, where 62% of households lost over half of their annual income. While social welfare and climate-smart agriculture programs exist, the coverage and adoption rates vary widely across communes. The findings highlight the disproportionate impacts on marginalized populations and the need for tailored, culturally-sensitive adaptation strategies. The study recommends promoting multipurpose tree planting, establishing community-based nurseries, diversifying livelihoods through small-scale family activities, and expanding inclusive financial mechanisms to enhance resilience. Findings from this study provide new insights into the complex vulnerabilities of ethnic minority communities in mountainous regions and offers targeted interventions to safeguard their livelihoods under accelerating climate change.